Body appreciation and its psychological correlates: A systematic review and meta-analysis. (September 2022) - Linardon, Jake; McClure, Zoe; Tylka, Tracy L.; Fuller-Tyszkiewicz, Matthew
Abstract: Body appreciation, defined as accepting, holding favourable attitudes towards, and respecting the body, is the most widely studied facet of positive body image. Despite more than 15 years of research investigating associations between body appreciation and psychological wellbeing constructs, a synthesis of this literature has yet to be performed. We conducted the first systematic review and meta-analysis of research on body appreciation and its psychological correlates. Two-hundred-forty papers were included, of which only eight investigated prospective associations. Random effects meta-analyses were performed on 35 cross-sectional correlates of body appreciation. Prospective associations were reviewed qualitatively. Meta-analyses showed that body appreciation was inversely associated with numerous indices of eating (eating pathology, restraint) and body image disturbances (appearance-ideal internalization, body surveillance, sociocultural pressures), and general psychopathology (depression, anxiety). Body appreciation was positively associated with several adaptive wellbeing constructs (self-esteem, self-compassion, sexual satisfaction). Crucially, pooled associations were still evident after controlling for the influence of negative body image. Qualitative synthesis showed that body appreciation may also promote better wellbeing over time. Findings confirm that body appreciation is consistently associated with better psychological wellbeing. Body appreciation shows promise as a viable intervention target in mental health promotion initiatives and eating disorder prevention programs. Highlights: A meta-analysis of body appreciation and its correlates was performed from 240 papers. Meta-analyses revealed negative correlations between body appreciation and psychopathology constructs. Meta-analyses revealed positive correlations between body appreciation and wellbeing constructs. Associations were not explained by negative body image. Body appreciation may be a viable intervention target.